Questions of professional ethics in the work a law enforcement officer - Bayandina, M.O. (Journal of actual problems of jurisprudence, 2018)
The article deals with professional ethics and moral issues of the choice of a law enforcement officer in professional activities. The question of duty, the strengthening of the rule of law, improving the service culture. Shown are the moral values of duty law enforcement officer, which is expressed in the conservation and protection of the rights and freedoms of man and citizen. Actualized moral essence of serving law enforcement community and the state, as one of the most important factors of training people to respect the law. Key words: professional ethics, moral obligation, duty, antinorms, moral behavior, the category of ethics, moral principles, norms.